ATF3‐Mediated NRF2/HO‐1 Signaling Regulates TLR4 Innate Immune Responses in Mouse Liver Ischemia/Reperfusion Injury. Issue 1 (30th October 2014) - Rao, J.; Qian, X.; Li, G.; Pan, X.; Zhang, C.; Zhang, F.; Zhai, Y.; Wang, X.; Lu, L.
<x xml:space="preserve">Abstract</x> Activating transcription factor 3 (ATF3) is a stress‐induced transcription factor that has been shown to repress inflammatory gene expression in multiple cell types and diseases. However, little is known about the roles and mechanisms of ATF3 in liver ischemia/reperfusion injury (IRI). In warm and cold liver IRI models, we showed that ATF3 deficiency significantly increased ischemia/reperfusion (IR)‐stressed liver injury, as evidenced by increased serum alanine aminotransferase levels, histological liver damage, and hepatocellular apoptosis. These may correlate with inhibition of the intrahepatic nuclear factor erythroid‐derived 2‐related factor 2/heme oxygenase‐1 (NRF2/HO‐1) signaling pathway leading to enhancing Toll‐like receptor 4/nuclear factor kappa beta (TLR4/NF‐κB) activation, pro‐inflammatory programs and macrophage/neutrophil trafficking, while simultaneously repressing anti‐apoptotic molecules in ischemic liver. Interestingly, activation of NRF2/HO‐1 signaling using an NRF2 activator, oltipraz (M2), during hepatic IRI‐rescued ATF3 anti‐inflammatory functions in ATF3‐deficient mice. For in vitro studies, ATF3 ablation in lipopolysaccharide (LPS)‐stimulated bone marrow‐derived macrophages (BMMs) depressed levels of NRF2/HO‐1 and PI3K/AKT, resulting in enhanced TLR4/NF‐κB activation. Pretreatment of LPS‐stimulated BMMs with M2 increased NRF2/HO‐1 expression, promoted PI3K/AKT, which in turn suppressed TLR4/NF‐κB‐mediated proinflammatory mediators. Thus, our results first demonstrate ATF3‐mediated NRF2/HO‐1 signaling in the regulation of TLR4‐driven inflammatory responses in IR‐stressed livers. Our findings provide a rationale for a novel therapeutic strategy for managing IR‐induced liver injury.